Framing Themes of Palm Oil in Google Images English-Language Advertisements - Bapoo, Lilisuriani Binti Abdul Latif @; Radzi, Muhammad `Izzat Bin Mohd (Journal of Ecohumanism, 2024)
The need to analyse the framing themes used for palm oil in a language largely used by business professionals which is English, is a response to the implementation of RED II and other related policy changes that have affected the palm oil industry since 2018. This study examines the framing themes employed in English-language palm oil advertisements post-2018, sourced from Google Images, utilising a content analysis approach. The study aims to investigate the framing themes employed in English-language palm oil advertisements sourced from Google Image Findings reveal that there are positive and negative framings used, influenced by geopolitical factors. The study contributes to our understanding of how palm oil and palm oil industry are portrayed in advertisements, offering valuable insights for policymakers, communication strategists, and researchers interested in the societal and environmental implications of this pivotal economic pillar of South-East Asian countries.